2007
DOI: 10.1007/s00018-007-7330-5
|View full text |Cite
|
Sign up to set email alerts
|

Melanocyte fate in neural crest is triggered by Myb proteins through activation of c-kit

Abstract: The c-myb proto-oncogene and its oncogenic derivative v-mybAMV encode transcriptional regulators engaged in the commitment of hematopoietic cells. While the c-Myb protein is important for the formation and differentiation of various progenitors, the v-MybAMV oncoprotein induces in chicks a progression and transformation of the single (monoblastic) cell lineage. Here we present the first evidence of cell fate-directing abilities of c-Myb and v-MybAMV proteins in avian neural crest (NC), where both proteins dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Thus, signaling pathways mediated by Wnts, FGFs, BMPs, c-Myb, and msh homeobox 1 (Msx-1) conspire to induce EMT (38)(39)(40). Among them, BMP most prominently induces the migratory property of neural crest cells.…”
Section: Type 1 Emt: Emt During Implantation Embryogenesis and Orgamentioning
confidence: 99%
“…Thus, signaling pathways mediated by Wnts, FGFs, BMPs, c-Myb, and msh homeobox 1 (Msx-1) conspire to induce EMT (38)(39)(40). Among them, BMP most prominently induces the migratory property of neural crest cells.…”
Section: Type 1 Emt: Emt During Implantation Embryogenesis and Orgamentioning
confidence: 99%
“…A reporter construct containing the Kit promoter was activated when cotransfected with a MYB expression vector, providing further evidence of a role for Myb in the regulation of KIT (Hogg et al 1997). Overexpression of the proto-oncogene c-MYB in avian neural crest cells increased KIT and subsequent KITL-KIT signalling, transforming these cells into melanocytes and thereby establishing a role for c-MYB in KIT regulation (Karafiat et al 2007). Similarly, c-MYB knockdown in normal erythroid progenitor cells demonstrated that c-MYB is required for KIT expression in erythroid cells (Vegiopoulos et al 2006).…”
Section: Myb and Etsmentioning
confidence: 97%
“…In the colon, c-Myb is required for colonic crypt homeostasis, including the integrity, normal differentiation, and steady-state proliferation of colon epithelial stem cells and progenitors (48, 55, 56). Interestingly, c-Myb expression has been found to be important for neural progenitor cell proliferation and for maintenance of neural stem cell niche (57), and an involvement of c-Myb in melanocytes links it to the functions of neural crest cells (44). Clearly, the c- myb gene is widely expressed, and the c-Myb protein plays a role in many cell types, not just hematopoietic cells.…”
Section: The Two Faces Of Myb: a Regulator And An Oncogenementioning
confidence: 99%
“…However, evidence of transformation by the v-Myb proteins is restricted to hematopoietic (157) and some neural crest cells (44). Since Myb proteins are transcription factors, the oncogenic activity is presumably linked to the activation or repression of specific target genes.…”
Section: Does Myb Regulate Differentiation Proliferation or Both?mentioning
confidence: 99%